E-Health Insurance Management System: Exploratory Research - Nahid, Md. Mehzabul Hoque; Zahid, Arnab; Hasan, Md. M. (AIUB Journal of Business and Economics, 2019)
Being an intermediary, insurers are one of the key players of healthcare industry and the link has formed in between insurance and healthcare through health insurance. The convergence of information and communication technology along with cyber physical environment has already started to establish. As opposed to, the insurance industry has also apprehended and started transforming. The purpose of this review is concisely presenting the contemporary technological scenario of health insurance. As the implication of cyber physical environment seems to have started in the insurance industry, the methodology has been formulated under three strategies (e.g. evidence searching, filtering and describing) to sort out the most validated, authentic and updated sources regarding the health insurance technology. Even though, synthesizing with evolving technologies like big data, cloud computing, IoT and other digital trends depicted in this study has seen to be used in insurance industry; the substantial usage of these technology has been observed very few for insurance management systems. It is expected that the study will aid to illustrate a comprehensive view of today’s technological scenario of health insurance and effort towards further related researches.